2020
DOI: 10.3390/jcm9061612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Mass Index on Postoperative Nausea and Vomiting: Propensity Analysis

Abstract: The impact of body mass index (BMI) on postoperative nausea and vomiting (PONV) is controversial, and few studies have focused on their relationship. We investigated the effects of BMI on PONV, taking into account other PONV risk factors. We analyzed adults over the age of 18 years who received general anesthesia between 2015 and 2019, using propensity score matching. Before propensity score matching, odds ratios (ORs) for PONV were lower for overweight (OR, 0.91; 95% confidence interval (CI), 0.87–0.96; p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
2
10
0
4
Order By: Relevance
“…In the current study, the number of overweight patients was 72 (41.4%), whereas obesity was noted in 52 (29.9%). Therefore, the relatively high percentage of patients with abnormally increased weight, as compared to the abovementioned literature, might have contributed to the final low incidence of low overall PONV, supporting the theory of Kim et al [31].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the current study, the number of overweight patients was 72 (41.4%), whereas obesity was noted in 52 (29.9%). Therefore, the relatively high percentage of patients with abnormally increased weight, as compared to the abovementioned literature, might have contributed to the final low incidence of low overall PONV, supporting the theory of Kim et al [31].…”
Section: Discussionsupporting
confidence: 65%
“…As only 1.6% of subjects were obese in the study of Nitahara et al [18], which showed a decreased incidence of PONV in this group of patients, in contrast to 10.1% in the review of Kranke et al [30], the conclusion regarding no influence of BMI > 30 on the rate of PONV is convincing. Kim et al [31], in their study of 113,881 patients who underwent GA, showed that an increased BMI reduced the incidence of PONV [26], whereas being underweight did not. In the current study, the number of overweight patients was 72 (41.4%), whereas obesity was noted in 52 (29.9%).…”
Section: Discussionmentioning
confidence: 99%
“…However, this opinion has been doubted over the past several years, and many studies have found opposite results (22)(23)(24)(25). In a recent large-scale study, Kim et al (25) performed propensity score matching for 103,561 patients who underwent general anesthesia. The results showed that (27).…”
Section: Discussionmentioning
confidence: 99%
“…Ukai et al identified female sex, lower BMI, and use of opioids through an epidural catheter as factors likely to affect the occurrence of PONV (12). However, there are also results showing that increased BMI is not a risk factor of PONV (19).…”
Section: Discussionmentioning
confidence: 99%